THE ROLE OF ENGLISH LANGUAGE SKILLS FOR TECHNICAL STUDENTS (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2026)
English language proficiency is increasingly recognized as a fundamental skill for technical students worldwide. In modern education and professional environments, technical students are required to comprehend technical manuals, scientific articles, research papers, and online instructional materials that are predominantly in English. This article explores the critical role of English language skills in facilitating academic success, enhancing professional communication, and supporting career development in technical fields.